40th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2004
DOI: 10.2514/6.2004-4054
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Rocket Motor Stability Prediction: Limit Amplitude, Triggering, and Mean Pressure Shift

Abstract: High-amplitude pressure oscillations in solid propellant rocket motor combustion chambers display nonlinear effects including: 1) limit cycle behavior in which the fluctuations may dwell for a considerable period of time near their peak amplitude, 2) elevated mean chamber pressure (DC shift), and 3) a triggering amplitude above which pulsing will cause an apparently stable system to transition to violent oscillations. Along with the obvious undesirable vibrations, these features constitute the most damaging im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…[11][12][13][14][15] An important conclusion of these studies is that systems that have linear heat release rate and nonlinear gas dynamics from first to third order do not exhibit subcritical bifurcations. 16 As well as in the above references, nonlinear heat release has been examined by Refs.…”
Section: Sources Of Nonlinearitymentioning
confidence: 99%
“…[11][12][13][14][15] An important conclusion of these studies is that systems that have linear heat release rate and nonlinear gas dynamics from first to third order do not exhibit subcritical bifurcations. 16 As well as in the above references, nonlinear heat release has been examined by Refs.…”
Section: Sources Of Nonlinearitymentioning
confidence: 99%
“…Flandro et al [5] also have demonstrated a predictive algorithm for DCshift based on the comprehensive nonlinear combustion instability models. Their analysis includes very complicated nonlinear models such as steep-fronted, shock pressure waves, e¨ects of irrotational §ow interactions, combustion coupling effects, and pressure coupling with the oscillatory §ow ¦eld.…”
Section: Introductionmentioning
confidence: 99%
“…local burning-through of the rocket case; (iii) propellant cracking; (iv) overpressure and breakage of the case induced by nozzle blocking or bore choking. The combustion instabilities were studied in detail in the classical papers of (Culick & Yang, 1992;Culick, 1996) and (Flandro et al, 2004). Bore choking phenomenon due to radial deformation of the propellant grain near booster joint segments was studied numerically in (Dick et al, 2005;Isaac & Iverson, 2003;Wang et al, 2005) and observed in primary construction of the Titan IV (see the report, Wilson at al., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The FD&P system can be developed using the fact that many fault modes of the SRMs have unique dynamical features in the time-traces of gas pressure, accelerometer data, and dynamics of nozzle gimbal angle. Indeed, analysis shows that many fault modes leading to SRMs failures, including combustion instabilities (Culick,1974;Culick & Yang, 1992;Culick,1996;Flandro et al, 2004), bore choking (Dick et al, 2005;Isaac & Iverson, 2003;Wang et al, 2005), propellant cracking, nozzle blocking, and case breach (Rogers, 1986), have unique dynamical features in the time-traces of pressure and thrust. Ideally, the corresponding expert knowledge could be incorporated into on-board FD&P within a general Bayesian inferential framework allowing for faster and more reliable identification of the off-nominal regimes of SRMs operation in real time.…”
Section: Introductionmentioning
confidence: 99%